Hydrologic control on winter dissolved oxygen mediates arsenic cycling in a small subarctic lake. Issue Volume 66:Issue S1(2021) Supplement (3rd August 2020) - Palmer, Michael J.; Chételat, John; Jamieson, Heather E.; Richardson, Murray; Amyot, Marc
Abstract: The seasonal development of an ice cover is a characteristic feature of subarctic lakes, yet the biogeochemical cycling of redox sensitive elements under ice, including arsenic (As), is poorly understood. We conducted comprehensive geochemical characterization of lake waters, sediment pore waters and lake sediments over two consecutive years to develop a conceptual model of As, iron (Fe), and sulfur (S) dynamics under ice in a shallow subarctic lake (mean depth 2.0 m) impacted by more than 60 yr of As pollution from local gold mining emissions. Lake sediments were a source of As to overlying waters during both winters when oxygen was depleted from interfacial sediments through the reductive dissolution of As‐bearing Fe (oxy)hydroxides, but the influence on lake water chemistry was distinctly different between years and dependent on winter hydrology of the lake. When the lake was hydrologically disconnected from the upstream watershed, anoxia developed through the entire water column and high concentrations of As (> 100  μ g L −1 ) and Fe (> 1000  μ g L −1 ) were measured in lake water. During the second winter, open‐water flow persisted at the lake inlet, which replenished dissolved oxygen in the under‐ice water column, suppressed the upward migration of the Fe and SO4 redox boundaries, and limited sediment As efflux. These findings demonstrate how changing hydrology, specifically ice cover duration, and hydrological connectivity can influence the winter cycling of As, Fe, and S in shallow subarctic lakes.